Faktor yang Mempengaruhi Keputusan Pemilihan Perguruan Tinggi Swasta (Studi pada Universitas Muria Kudus) - Indah Dwi Prasetyaningrum; Etni Marliana (JEMBATAN, 2020)
In recent years, many changes have occurred regarding the condition of higher education. Formerly, to study in higher education is considered as a prestigious thing. However, these days, higher education has been seen as a necessity for the community be able to improve social and economic conditions. This state, increase the number of private universities every year in every region of Indonesia. In Kudus, there were only one private university namely Universitas Muria Kudus. However, today there is another private university in the city. The emergence of another private university in Kudus will increase the competition to get new students. In order to compete with the new private university, it is needed to know factors that influence someone in the university choice. In this research there are four factors that could affect the university choice (1) characteristic of university, (2) quality and facility of university, (3) external factor, and (4) marketing/communication factor. Questionnaire result will be used as primary data in this research. The respondents for this research are 344 students that were on the first semester of all faculties in UMK. Proportional random sampling method is use to determine research sample.  Result of the study show that quality and facility of university and marketing/communication factor each has positive and significant influence towards university choice. Meanwhile characteristic of university and external factor each has positive but not significant influence toward university choice.